Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

prove that 1/(sec x -tan x)-1/cos x = 1/cos x - 1/(sec x + tan x )

Asked by 10th August 2012, 5:47 PM
Answered by Expert
Answer:
LHS = 1/(sec x -tan x)-1/cos x
= sec x + tan x/(sec x - tan x)(sec x + tan x) - 1/cos x
= sec x + tan x/(sec2x - tan2x) - 1/cos x
= sec x + tan x - sec x
= tan x
 
RHS = 1/cos x - 1/(sec x + tan x)
1/cos x - (sec x - tan x)/(sec x + tan x) (sec x - tan x)
= 1/cos x - (sec x - tan x)/(sec2x - tan2x)
= sec x - (sec x - tan x)/1
= sec x - sec x + tan x
= tan x
 
Hence, LHS = RHS
Answered by Expert 10th August 2012, 9:31 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Latest Questions

Chat with us on WhatsApp